Temperate Forest Floors: Ecosystem Hubs in Transition? - Friederike Lang; Jörg Prietzel; Frank Hagedorn; Klaus Kaiser; Stefanie Schulz; Mathias Mayer; Lars Vesterdal; Jürgen Bauhus; Maï Bergmann; Sebastian Bibinger; Martin I. Bidartondo; Jingxuan Olivia Chen; et al. (Global Change Biology, 2026)
The forest floor (FF) plays a key role in carbon, nutrient, and water cycling. It is the biologically most active compartment of forest soils, highly responsive to environmental conditions. Yet, its response to current changes in environmental conditions and forest management is understudied. Temperate forests are among the best studied ecosystems globally, providing the necessary ecological and biogeochemical background information to assess FF changes. Here, we focus on identifying existing knowledge and gaps in our understanding of the functioning of the FF. Interactions between FF biota and abiotic FF components show multifactorial dependencies with environmental conditions and drive FF turnover. Vice versa, the turnover of FF regulates carbon, nutrient, and water cycling. With slow litter decomposition and limited bioturbation, organic matter accumulates, nutrients cycle tightly within the FF, and water passes through this layer partly along preferential pathways. With rapid litter decomposition and intense bioturbation, FF accumulation is little, the mineral soil is the main nexus for plant nutrient uptake and organic matter transformation, and water infiltrates the mineral soil more homogeneously. The interconnectedness with the adjacent ecosystem compartments is a crucial feature of the FF, feeding back to its functioning and making it a central hub of forest processes. The FF morphology reflects these processes and therefore has untapped potential as an indicator of soil and ecosystem health. Under forest change, the FF might lose its functionality, with negative impacts on nutrient provision, water storage, and carbon sequestration. Consequences for forest growth could be strong and even detrimental. Hence, improved knowledge of FF characteristics and their linkages to mineral soils and aboveground ecosystem compartments is crucial for assessing forest resilience to progressing environmental changes.

Windthrow disturbance impacts soil biogeochemistry and bacterial communities in a temperate forest - Bonnie G. Waring; Lena Lancastle; Thomas Bell; Martin I. Bidartondo; Pablo García-Díaz; Xavier Lambin; Elena Vanguelova; Francis A. Windram (Plant and Soil, 2025)
Aims Forests across the world are subject to disturbance via wind, wildfire, and pest and disease outbreaks. Yet we still have an incomplete understanding of how these stressors impact forest biota—particularly the soil microbes, which govern forest carbon and nutrient cycling. Methods Here, we investigated the impact of a severe windstorm on soil bacterial communities in Kielder Forest, a temperate coniferous forest in the north of England. Within ten individual sites, defined by common stand composition and topography, we established 50 m 2 plots in undisturbed stands, and in nearby stands that were moderately and/or severely disturbed by windthrow. Soils were sampled within each of the 22 study plots, and analysed for changes in carbon and nitrogen content, pH, root biomass, and bacterial community structure. We separately sequenced bacteria from bulk soils, rhizosphere soils, and root tissues to assess whether disturbance impacts varied based on the proximity of microbiota to tree roots. Results Less than a year after the storm, we found that the most severely disturbed stands had lower canopy cover, lower soil carbon content, higher soil pH, and a smaller fine root biomass than the undisturbed stands. Disturbance also impacted bacterial community beta-diversity, but the effects were subtle and did not vary among assemblages in bulk vs. rhizosphere soils. Conclusions Impacts of aboveground disturbance on soil biogeochemistry can be significant, but soil bacterial communities are relatively well-buffered against these changes. However, altered patterns of root growth and carbon cycling may have longer-term implications for forest recovery after windthrow disturbances.

Fruitbody and root data infer different environmental niches for ectomycorrhizal fungi - Muyao Qi; Laura M. Suz; Martin I. Bidartondo; C. David L. Orme; Guillaume Delhaye; Isabel Openshaw; Carolina Tovar (Journal of Biogeography, 2024)
Aim We used two fungal data sources for occurrence records (fruitbodies and roots) to (1) test the influence of data source on estimating the environmental niche of ectomycorrhizal (ECM) fungi and (2) compare the differences in estimated niche area and density for ECM fungal species with conspicuous (easily observed, i.e. mushrooms) versus inconspicuous (difficult to observe and/or usually overlooked, i.e. crusts and truffles) fruitbodies. Location Europe. Taxon Sixty‐six ectomycorrhizal fungi. Methods We used fungal records obtained from fruitbody and root data of 66 common ECM fungal species in European forests to estimate their environmental niches. The fruitbody data were extracted from public databases (GBIF, UNITE), while the root data (from individual ectomycorrhizas) were obtained from a dataset of 136 ICP Forests long‐term intensive monitoring plots. We estimated the niches for combined data sources (fruitbody and root data) and for each individual data source using six key environmental variables for ECM fungal community composition. We then examined how estimated niche overlap and area (number of cells in niche grid) varied for the two data sources between conspicuous and inconspicuous species. Results We found that although the niches estimated using combined data from the two data sources had high overlap with the niches estimated from fruitbody data, the niches estimated from fruitbody data had low or medium overlap with the niches estimated using root data for most ECM fungi. The overlap between the two data sources for conspicuous species was significantly larger than that for inconspicuous species. Root data were important for estimating the niche of inconspicuous species, which had a high ratio of root data to fruitbody data. Main Conclusion Our results indicate that although fruitbody data suffice for estimating the environmental niche for most conspicuous ECM fungi, combined datasets including fruitbody and root data can improve the accuracy of estimated niches and should be used. Root data for inconspicuous species are particularly useful, and thus, adopting root data in niche estimation will better infer the niches of ECM fungi. Inferring niches along environmental variables can guide future sampling and conservation of fungi.

Ectomycorrhizal fungi are influenced by ecoregion boundaries across Europe - Guillaume Delhaye; Sietse van der Linde; David Bauman; C. David L. Orme; Laura M. Suz; Martin I. Bidartondo (Global Ecology and Biogeography, 2024)
Aim Ecoregions and the distance decay in community similarity are fundamental concepts in biogeography and conservation biology that are well supported across plants and animals, but not fungi. Here we test the relevance of these concepts for ectomycorrhizal (ECM) fungi in temperate and boreal regions. Location Europe. Time Period 2008–2015. Major Taxa Studied Ectomycorrhizal fungi. Methods We used a large dataset of ~24,000 ectomycorrhizas, assigned to 1350 operational taxonomic units, collected from 129 forest plots via a standardized protocol. We investigated the relevance of ecoregion delimitations for ECM fungi through complementary methodological approaches based on distance decay models, multivariate analyses and indicator species analyses. We then evaluated the effects of host tree and climate on the observed biogeographical distributions. Results Ecoregions predict large‐scale ECM fungal biodiversity patterns. This is partly explained by climate differences between ecoregions but independent from host tree distribution. Basidiomycetes in the orders Russulales and Atheliales and producing epigeous fruiting bodies, with potentially short‐distance dispersal, show the best agreement with ecoregion boundaries. Host tree distribution and fungal abundance (as opposed to presence/absence only) are important to uncover biogeographical patterns in mycorrhizas. Main Conclusions Ecoregions are useful units to investigate eco‐evolutionary processes in mycorrhizal fungal communities and for conservation decision‐making that includes fungi.

Carbon for nutrient exchange between Lycopodiella inundata and Mucoromycotina fine root endophytes is unresponsive to high atmospheric CO2 - Grace A. Hoysted; Jill Kowal; Silvia Pressel; Jeffrey G. Duckett; Martin I. Bidartondo; Katie J. Field (Mycorrhiza, 2021)
Non-vascular plants associating with arbuscular mycorrhizal (AMF) and Mucoromycotina ‘fine root endophyte’ (MFRE) fungi derive greater benefits from their fungal associates under higher atmospheric [CO 2 ] (a[CO 2 ]) than ambient; however, nothing is known about how changes in a[CO 2 ] affect MFRE function in vascular plants. We measured movement of phosphorus (P), nitrogen (N) and carbon (C) between the lycophyte Lycopodiella inundata and Mucoromycotina fine root endophyte fungi using 33 P-orthophosphate, 15 N-ammonium chloride and 14 CO 2 isotope tracers under ambient and elevated a[CO 2 ] concentrations of 440 and 800 ppm, respectively. Transfers of 33 P and 15 N from MFRE to plants were unaffected by changes in a[CO 2 ]. There was a slight increase in C transfer from plants to MFRE under elevated a[CO 2 ]. Our results demonstrate that the exchange of C-for-nutrients between a vascular plant and Mucoromycotina FRE is largely unaffected by changes in a[CO 2 ]. Unravelling the role of MFRE in host plant nutrition and potential C-for-N trade changes between symbionts under different abiotic conditions is imperative to further our understanding of the past, present and future roles of plant-fungal symbioses in ecosystems.

Connecting high‐throughput biodiversity inventories: Opportunities for a site‐based genomic framework for global integration and synthesis - Paula Arribas; Carmelo Andújar; Martin I. Bidartondo; Kristine Bohmann; Éric Coissac; Simon Creer; Jeremy R. deWaard; Vasco Elbrecht; Gentile F. Ficetola; Marta Goberna; Susan Kennedy; Henrik Krehenwinkel; et al. (Molecular Ecology, 2021)
High‐throughput sequencing (HTS) is increasingly being used for the characterization and monitoring of biodiversity. If applied in a structured way, across broad geographical scales, it offers the potential for a much deeper understanding of global biodiversity through the integration of massive quantities of molecular inventory data generated independently at local, regional and global scales. The universality, reliability and efficiency of HTS data can potentially facilitate the seamless linking of data among species assemblages from different sites, at different hierarchical levels of diversity, for any taxonomic group and regardless of prior taxonomic knowledge. However, collective international efforts are required to optimally exploit the potential of site‐based HTS data for global integration and synthesis, efforts that at present are limited to the microbial domain. To contribute to the development of an analogous strategy for the nonmicrobial terrestrial domain, an international symposium entitled “Next Generation Biodiversity Monitoring” was held in November 2019 in Nicosia (Cyprus). The symposium brought together evolutionary geneticists, ecologists and biodiversity scientists involved in diverse regional and global initiatives using HTS as a core tool for biodiversity assessment. In this review, we summarize the consensus that emerged from the 3‐day symposium. We converged on the opinion that an effective terrestrial Genomic Observatories network for global biodiversity integration and synthesis should be spatially led and strategically united under the umbrella of the metabarcoding approach. Subsequently, we outline an HTS‐based strategy to collectively build an integrative framework for site‐based biodiversity data generation.

Prevalence and phenology of fine root endophyte colonization across populations of Lycopodiella inundata - Jill Kowal; Elena Arrigoni; Jordi Serra; Martin Bidartondo (Mycorrhiza, 2020)
Mycorrhizal fungi are critical components of terrestrial habitats and agroecosystems. Recently, Mucoromycotina fine root endophyte fungi (MucFRE) were found to engage in nutritional mutualism with Lycopodiella inundata , which belongs to one of the earliest vascular plant lineages known to associate with MucFRE. The extent to which this mutualism plays a role in resilient plant populations can only be understood by examining its occurrence rate and phenological patterns. To test for prevalence and seasonality in colonization, we examined 1305 individual L. inundata roots from 275 plants collected during spring and autumn 2019 across 11 semi-natural heathlands in Britain and the Netherlands. We quantified presence/absence of fine root endophyte (FRE) hyphae and vesicles and explored possible relationships between temperature and precipitation in the months immediately before sampling. Fine root endophyte hyphae were dominant in all of the examined heathlands, and every colonized root had FRE in both cortical cells and root hairs. However, we found significant differences in colonization between the two seasons at every site. Overall, 14% of L. inundata roots were colonized in spring (2.4% with vesicles) compared with 86% in autumn (7.6% with vesicles). Colonization levels between populations were also significantly different, correlating with temperature and precipitation, suggesting some local environments may be more conducive to root and related hyphal growth. These marked seasonal differences in host-plant colonization suggest that results about FRE from single time point collections should be carefully interpreted. Our findings are relevant to habitat restoration, species conservation plans, agricultural bio-inoculation treatments, and microbial diversity studies.

Recovery of mycorrhizal fungi from wild collected protocorms of Madagascan endemic orchid Aerangis ellisii (B.S. Williams) Schltr. and their use in seed germination in vitro - Jonathan P. Kendon; Kazutomo Yokoya; Lawrence W. Zettler; Alison S. Jacob; Faye McDiarmid; Martin I. Bidartondo; Viswambharan Sarasan (Mycorrhiza, 2020)
Orchid mycorrhizal fungi (OMF) are critical for seed germination and maintaining natural populations of orchids, yet the degree of specificity of most orchids to their mycorrhizal associates remains unknown. Many orchids are at risk of extinction, whether generalists or specialists, but orchid species of narrow fungal specificity are arguably under increased threat due to their requirement for specific fungal symbionts. This study characterises the fungi associated with Aerangis ellisii , a lithophytic orchid from a site in the Central Highlands of Madagascar. Culturable OMF isolated from spontaneous protocorms of this species from the wild were used for seed germination. In vitro germination and seedling development of A. ellisii were achieved with fungi derived from A. ellisii and an isolate from a different Aerangis species 30 km away. The significance of these findings and their importance to conservation strategies for this species and other Aerangis spp. is discussed. These results have important implications for the conservation of A. ellisii populations in Madagascar.

The distribution and evolution of fungal symbioses in ancient lineages of land plants - William R. Rimington; Jeffrey G. Duckett; Katie J. Field; Martin I. Bidartondo; Silvia Pressel (Mycorrhiza, 2020)
An accurate understanding of the diversity and distribution of fungal symbioses in land plants is essential for mycorrhizal research. Here we update the seminal work of Wang and Qiu (Mycorrhiza 16:299-363, 2006) with a long-overdue focus on early-diverging land plant lineages, which were considerably under-represented in their survey, by examining the published literature to compile data on the status of fungal symbioses in liverworts, hornworts and lycophytes. Our survey combines data from 84 publications, including recent, post-2006, reports of Mucoromycotina associations in these lineages, to produce a list of at least 591 species with known fungal symbiosis status, 180 of which were included in Wang and Qiu (Mycorrhiza 16:299-363, 2006). Using this up-to-date compilation, we estimate that fewer than 30% of liverwort species engage in symbiosis with fungi belonging to all three mycorrhizal phyla, Mucoromycota, Basidiomycota and Ascomycota, with the last being the most widespread (17%). Fungal symbioses in hornworts (78%) and lycophytes (up to 100%) appear to be more common but involve only members of the two Mucoromycota subphyla Mucoromycotina and Glomeromycotina, with Glomeromycotina prevailing in both plant groups. Our fungal symbiosis occurrence estimates are considerably more conservative than those published previously, but they too may represent overestimates due to currently unavoidable assumptions.

Evolution and networks in ancient and widespread symbioses between Mucoromycotina and liverworts - William R. Rimington; Silvia Pressel; Jeffrey G. Duckett; Katie J. Field; Martin I. Bidartondo (Mycorrhiza, 2019)
Like the majority of land plants, liverworts regularly form intimate symbioses with arbuscular mycorrhizal fungi (Glomeromycotina). Recent phylogenetic and physiological studies report that they also form intimate symbioses with Mucoromycotina fungi and that some of these, like those involving Glomeromycotina, represent nutritional mutualisms. To compare these symbioses, we carried out a global analysis of Mucoromycotina fungi in liverworts and other plants using species delimitation, ancestral reconstruction, and network analyses. We found that Mucoromycotina are more common and diverse symbionts of liverworts than previously thought, globally distributed, ancestral, and often co-occur with Glomeromycotina within plants. However, our results also suggest that the associations formed by Mucoromycotina fungi are fundamentally different because, unlike Glomeromycotina, they may have evolved multiple times and their symbiotic networks are un-nested (i.e., not forming nested subsets of species). We infer that the global Mucoromycotina symbiosis is evolutionarily and ecologically distinctive.

Light limitation and partial mycoheterotrophy in rhizoctonia-associated orchids - Julienne M.-I. Schweiger; Christian Kemnade; Martin I. Bidartondo; Gerhard Gebauer (Oecologia, 2019)

The Ninth International Conference on Mycorrhiza in Prague: across mycorrhizal symbioses from molecules to global scales - Martin I. Bidartondo; Mohamed Hijri (Mycorrhiza, 2018)

The biogeographical history of the interaction between mycoheterotrophic Thismia (Thismiaceae) plants and mycorrhizal Rhizophagus (Glomeraceae) fungi - Vincent S. F. T. Merckx; Sofia I. F. Gomes; Mark Wapstra; Colin Hunt; Greg Steenbeeke; Constantijn B. Mennes; Neville Walsh; Rob Smissen; Tsung‐Hsin Hsieh; Erik F. Smets; Martin I. Bidartondo (Journal of Biogeography, 2017)
Aim Achlorophyllous mycoheterotrophic plants and mycorrhizal fungi often have highly specific interactions that potentially limit the plants’ distribution and diversification potential. However, specificity in biotic interactions may differ considerably over a species’ distribution range and therefore interactions need to be studied over their entire range to assess their evolution in space and time. The present study investigates the biogeographical history of the interaction between five closely related mycoheterotrophic Thismia species and arbuscular mycorrhizal fungi over the distribution range of the plant species. Location Temperate south‐east Australia and New Zealand. Methods Phylogenetic relationships of Thismia (nr ITS and mt cob ) and their arbuscular mycorrhizal fungi (partial nr SSU ) were reconstructed based on data from 65 plant specimens. The diversification times in Thismia were estimated with a Bayesian relaxed clock approach using a Dioscoreales framework (nr SSU , mt atp1 , mt matR , mt nad1 b‐c ). Ancestral geographical ranges were reconstructed using a maximum likelihood approach. The same approach was used to reconstruct ancestral mycorrhizal associations. Results Our analysis shows that Thismia plants have highly specific, phylogenetically conserved and evolutionarily persistent interactions with Rhizophagus fungi. Nevertheless, Thismia was able to diversify and radiate recently due to the wide geographical distribution of the host fungi. In addition, we find that although the mycorrhizal interactions of this clade of mycoheterotrophs are strictly bound to a fungal lineage, host switches remain possible. Main conclusions In this clade of closely related mycoheterotrophs, dependency on highly specific fungal interactions is the result of phylogenetic niche conservatism, acting over at least 12 million years. Nevertheless, plants that are dependent on highly specific fungal interactions have ample opportunities to disperse and radiate over the geographical range of their hosts. Our study highlights the need to link the ecology and evolution of species interactions over broad geographical and evolutionary scales for understanding mycorrhizal interactions.

Preliminary findings on identification of mycorrhizal fungi from diverse orchids in the Central Highlands of Madagascar - Kazutomo Yokoya; Lawrence W. Zettler; Jonathan P. Kendon; Martin I. Bidartondo; Andrew L. Stice; Shannon Skarha; Laura L. Corey; Audrey C. Knight; Viswambharan Sarasan (Mycorrhiza, 2015)

Environmental drivers of ectomycorrhizal communities in Europe's temperate oak forests - Laura M. Suz; Nadia Barsoum; Sue Benham; Hans‐Peter Dietrich; Karl Dieter Fetzer; Richard Fischer; Paloma García; Joachim Gehrman; Ferdinand Kristöfel; Miklós Manninger; Stefan Neagu; Manuel Nicolas; et al. (Molecular Ecology, 2014)
Ectomycorrhizal fungi are major ecological players in temperate forests, but they are rarely used in measures of forest condition because large‐scale, high‐resolution, standardized and replicated belowground data are scarce. We carried out an analysis of ectomycorrhizas at 22 intensively monitored long‐term oak plots, across nine European countries, covering complex natural and anthropogenic environmental gradients. We found that at large scales, mycorrhizal richness and evenness declined with decreasing soil pH and root density, and with increasing atmospheric nitrogen deposition. Shifts in mycorrhizas with different functional traits were detected; mycorrhizas with structures specialized for long‐distance transport related differently to most environmental variables than those without. The dominant oak‐specialist Lactarius quietus, with limited soil exploration abilities, responds positively to increasing nitrogen inputs and decreasing pH . In contrast, Tricholoma , Cortinarius and Piloderma species , with medium‐distance soil exploration abilities, show a consistently negative response. We also determined nitrogen critical loads for moderate (9.5–13.5 kg N/ha/year) and drastic (17 kg N/ha/year) changes in belowground mycorrhizal root communities in temperate oak forests. Overall, we generated the first baseline data for ectomycorrhizal fungi in the oak forests sampled, identified nitrogen pollution as one of their major drivers at large scales and revealed fungi that individually and/or in combination with others can be used as belowground indicators of environmental characteristics.

The Role of Botanic Gardens in the Science and Practice of Ecological Restoration - KATE A. HARDWICK; PEGGY FIEDLER; LYNDON C. LEE; BRUCE PAVLIK; RICHARD J. HOBBS; JAMES ARONSON; MARTIN BIDARTONDO; ERIC BLACK; DAVID COATES; MATTHEW I. DAWS; KINGSLEY DIXON; STEPHEN ELLIOTT; et al. (Conservation Biology, 2011)
Many of the skills and resources associated with botanic gardens and arboreta, including plant taxonomy, horticulture, and seed bank management, are fundamental to ecological restoration efforts, yet few of the world's botanic gardens are involved in the science or practice of restoration. Thus, we examined the potential role of botanic gardens in these emerging fields. We believe a reorientation of certain existing institutional strengths, such as plant‐based research and knowledge transfer, would enable many more botanic gardens worldwide to provide effective science‐based support to restoration efforts. We recommend botanic gardens widen research to include ecosystems as well as species, increase involvement in practical restoration projects and training practitioners, and serve as information hubs for data archiving and exchange.

Nitrogen availability is a primary determinant of conifer mycorrhizas across complex environmental gradients - Filipa Cox; Nadia Barsoum; Erik A. Lilleskov; Martin I. Bidartondo (Ecology Letters, 2010)
Ecology Letters (2010) 13: 1103–1113 Abstract Global environmental change has serious implications for functional biodiversity in temperate and boreal forests. Trees depend on mycorrhizal fungi for nutrient uptake, but predicted increases in nitrogen availability may alter fungal communities. To address a knowledge gap regarding the effects of nitrogen availability on mycorrhizal communities at large scales, we examine the relationship between nitrogen and ectomycorrhizas in part of a European biomonitoring network of pine forest plots. Our analyses show that increased nitrogen reduces fungal diversity and causes shifts in mycorrhizal community composition across plots, but we do not find strong evidence that within‐plot differences in nitrogen availability affect ectomycorrhizal communities. We also carry out exploratory analyses to determine the relative importance of other environmental variables in structuring mycorrhizal communities, and discuss the potential use of indicator species to predict nitrogen‐induced shifts in fungal communities.

Fungal specificity bottlenecks during orchid germination and development - MARTIN I. BIDARTONDO; DAVID J. READ (Molecular Ecology, 2008)
Fungus‐subsidized growth through the seedling stage is the most critical feature of the life history for the thousands of mycorrhizal plant species that propagate by means of ‘dust seeds.’ We investigated the extent of specificity towards fungi shown by orchids in the genera Cephalanthera and Epipactis at three stages of their life cycle: (i) initiation of germination, (ii) during seedling development, and (iii) in the mature photosynthetic plant. It is known that in the mature phase, plants of these genera can be mycorrhizal with a number of fungi that are simultaneously ectomycorrhizal with the roots of neighbouring forest trees. The extent to which earlier developmental stages use the same or a distinctive suite of fungi was unclear. To address this question, a total of 1500 packets containing orchid seeds were buried for up to 3 years in diverse European forest sites which either supported or lacked populations of helleborine orchids. After harvest, the fungi associated with the three developmental stages, and with tree roots, were identified via cultivation‐independent molecular methods. While our results show that most fungal symbionts are ectomycorrhizal, differences were observed between orchids in the representation of fungi at the three life stages. In Cephalanthera damasonium and C. longifolia , the fungi detected in seedlings were only a subset of the wider range seen in germinating seeds and mature plants. In Epipactis atrorubens , the fungi detected were similar at all three life stages, but different fungal lineages produced a difference in seedling germination performance. Our results demonstrate that there can be a narrow checkpoint for mycorrhizal range during seedling growth relative to the more promiscuous germination and mature stages of these plants’ life cycle.